The Constitutional regularity parameter asan instrumento to guarantee human rights in the face of procedural formalities: Jurisprudential and case analysis - Reynoso Serrano, Rafael (UNIVERSIDAD DE SONORA, 2017)
Constitutional reforms on human rights have been the basis for judges to interpret laws according to the needs of social reality. With the establishment of the constitutional regularity parameter, the doors have been opened for judges to resolve disputes in an increasingly just way, since they are not bound by formal limitations that sometimes do not have a practical purpose or do not benefit the parties on trial. Therefore, the objective of this paper is to analyze the jurisprudential status that prevails in human rights issues and their restrictions, in order to be able to weigh in which cases a procedural formality constitutes a disproportionate restriction of some constitutionally protected right, using a practical case as an example.